Adherence to the Mediterranean diet and gastric cancer risk in Italy. Issue 12 (5th December 2013) - Praud, Delphine; Bertuccio, Paola; Bosetti, Cristina; Turati, Federica; Ferraroni, Monica; La, Carlo
<x xml:space="preserve">Abstract</x> We investigated gastric cancer risk in relation to the adherence to the Mediterranean diet using data from two case–control studies conducted in Italy between 1985 and 2007, including 999 incidents, histologically confirmed gastric cancers and 2, 628 controls admitted to hospital for acute non‐neoplastic diseases. Adherence to the Mediterranean diet was assessed using the Mediterranean Diet Score (MDS) based on nine of the major characteristics of the Mediterranean diet in the overall dataset. The Mediterranean Dietary Pattern adherence index (MDP) and the Mediterranean Adequacy Index (MAI) were considered in the second study only. We estimated odds ratios (OR) and corresponding 95% confidence intervals (CI) of gastric cancer for categories of the three scores using multiple logistic regression models. We found a reduced risk of gastric cancer for increasing levels of the MDS: as compared to subjects in the lowest category of the MDS, the ORs were 0.78, 0.61 and 0.57 in subsequent levels of MDS, with a significant trend in risk. Risk estimates were consistent across strata of age, sex, education, smoking, body mass index, and family history of gastric cancer. We also observed a decreased risk of gastric cancer for the highest versus the lowest quintile for MDP and MAI, with OR of 0.58 and 0.71, respectively. Our study provides convincing evidence of a beneficial role of the Mediterranean diet on gastric cancer.